Penentuan strategi pemasaran aplikasi e-commerce menggunakan game Theory - Fijri Arrofilah, Syifa; Sofhya, Herlinda Nur’afwa (Kreasi Pustaka Mandiri (Krestama), 2025)
Online shopping activities have recently increased significantly, resulting in consumers who initially shopped at offline stores switching to online stores through e-commerce applications, which are currently experiencing intense competition. In the face of fierce competition in the global business world, every company needs to develop a strategic marketing plan to enhance business quality and achieve its goals. This study aims to identify the attributes that are most important to consumers in each e-commerce application, determine the value of the game, and identify the optimal e-commerce marketing strategy using game Theory. This study utilises two e-commerce applications, namely Tokopedia and Shopee, and employs eight strategies: product, place, price, delivery speed, promotion, practicality, website appearance, and security. The marketing strategy used is a mixed approach, utilising POM QM Software for Windows V4 for support. The results obtained from the competition between Tokopedia and Shopee indicate that the optimal strategy for Tokopedia is a combination of price and promotion. In contrast, the optimal strategy for Shopee is a combination of promotion and security. According to the research results above, the attribute that is emphasised in each e-commerce application is the promotion strategy.